2011
DOI: 10.1037/a0020730
|View full text |Cite
|
Sign up to set email alerts
|

Being bicultural: A mixed-methods study of adolescents' implicitly and explicitly measured multiethnic identities.

Abstract: Understanding how ethnic identities develop in adolescence is currently limited by a reliance on self-report paper-and-pencil measures. This mixed-methods study presents a novel response time measure, the Multiethnic Identities Processing Task (MIPT), to quantify bicultural adolescents' implicit identifications with ethnic and racial identity labels. Eighty-four adolescents (age 14-21 years) of diverse ethnic and racial backgrounds self-identified as bicultural or not bicultural and described their ethnic iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 113 publications
3
22
0
1
Order By: Relevance
“…"Most Americans think that we don't exist" (12-year-old Mexican boy). (M. Suárez-Orozco & Suárez-Orozco, 2000, p. 27) In our own research with mixed-ethnic and mixed-racial second-generation immigrant adolescents, we also saw qualitative evidence of the power of social mirroring for shaping ethnic identities (Marks, Patton, & García Coll, 2011). When asked why a student provided the low rating of "pride" in the cultural immigrant group she selected, one student told us: I don't know because when I was little there were a lot of Chinese jokes and I'd feel like "Oh being Chinese, they make fun of Chinese and so they are not as good as Americans."…”
Section: Immigration As a Context And The Role Of Social Mirroringmentioning
confidence: 76%
“…"Most Americans think that we don't exist" (12-year-old Mexican boy). (M. Suárez-Orozco & Suárez-Orozco, 2000, p. 27) In our own research with mixed-ethnic and mixed-racial second-generation immigrant adolescents, we also saw qualitative evidence of the power of social mirroring for shaping ethnic identities (Marks, Patton, & García Coll, 2011). When asked why a student provided the low rating of "pride" in the cultural immigrant group she selected, one student told us: I don't know because when I was little there were a lot of Chinese jokes and I'd feel like "Oh being Chinese, they make fun of Chinese and so they are not as good as Americans."…”
Section: Immigration As a Context And The Role Of Social Mirroringmentioning
confidence: 76%
“…Finally, results of the exploration of the third question revealed that CBRI did not significantly moderate the relationship between discrimination and MII, despite the reasonable expectation, based on the literature, that it would (Brewster et al, 2013; Costarelli, 2011; Costarelli & Gerłowska, 2015). This lack of effect could again point to the idea that color‐blindness manifests differently in multiracial people than it does in monoracial minority people, possibly because of the widely varying types and experiences of multiracial people (Giamo et al, 2012; Jackson et al, 2012; Marks et al, 2011; Offermann et al, 2014; Rockquemore et al, 2009), and should be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Jackson et al (2012) investigated the relationships among MII, perceived discrimination, and psychological adjustment and concluded that experiences of perceived racial discrimination are a risk factor for multiracial individuals and that having an integrated multiracial identity could serve as a protective factor for psychological adjustment. The beginnings of this type of research inquiry have made clear the complexity of multiracial identity (Marks, Patton, & Coil, 2011; Rockquemore et al, 2009) and its relationship to mental health, discrimination, and racial attitudes (Giamo et al, 2012; Jackson et al, 2012; Offermann et al, 2014). The extent to which multiracial identity is related to mental health, discrimination, and racial attitudes must be considered to further the understanding of multiracial individuals and the counseling profession.…”
mentioning
confidence: 99%
“…Lorsqu'elle est associée à une culture en particulier, on parle alors d'identité culturelle, c'est-à-dire de l'ensemble des éléments d'une culture par lesquels un individu ou un groupe se définissent ou se distinguent des autres (Abou, 1986). Pour les élèves issus de la diversité, il est aussi souvent question d'identité pluri-ou multi-culturelle, qui renvoie à la capacité individuelle de se définir et de s'accepter en tant que membres de plus d'un groupe ethnoculturel (Marks, Patton et Coll, 2011).…”
Section: Dimension 5 Le Soutien à La Construction Identitaire Des Jeunclassified